Pentingnya metodologi penelitian dalam pastoral berbasis data di keuskupan Surabaya - Yohanes Benny Suwito; Yustinus Budi Hermanto; Christina Esti Susanti; Bernadus Aris Ferdinan (Jurnal Komunikasi Profesional, 2022)
The background of the community service program is to provide awareness for young priests in the Surabaya Diocese about the importance of data. Data is an important thing that can be used as a basis for decision making. Therefore, it is necessary to provide an understanding of a data and how to read the data. The methods used in this community service are 1) teaching about research methodology, and 2) training in data processing and reading data using the Statistical Package for the Social Sciences (SPSS) and Structural Equation Modeling (SEM). The result of this community service program is that young priests in the Surabaya Diocese become more aware, understand, and can make decisions based on data so that they are able to carry out data-based parish services.